Luminescence properties of Na3LuSi3O9:Ce3+ as a potential scintillator material. Issue 124 (30th November 2015) - Zhou, Jianbang; Pan, Fengjuan; Zhong, Jiuping; Liang, Hongbin; Su, Qiang; Moretti, Federico; Lebbou, Kheirreddine; Dujardin, Christophe
Abstract : Comparison between the X-ray excited luminescence spectra of the Bi4 Ge3 O12 (BGO) and Na3 Lu0.99 Ce0.01 Si3 O9 powders. Abstract : Lutetium based oxyorthosilicate (Lu2 SiO5 :Ce 3+ /Lu2− x Y x SiO5 :Ce 3+ ) and pyrosilicate (Lu2 Si2 O7 :Ce 3+ ) scintillators exhibit good scintillation performances in terms of light-yield and decay properties. Nevertheless, both of them have a high melting point (≥1900 °C) which is unfavorable to crystal growth. In this work, an alternative lutetium based silicate scintillator was proposed with a lower melting point (about 1500 °C): Na3 LuSi3 O9 :Ce 3+ . The structure and thermal quenching properties of Na3 LuSi3 O9 :Ce 3+ were investigated. The emission spectra of Na3 Lu0.99 Ce0.01 Si3 O9 under UV and X-ray excitation as well as pulsed X-ray measurements were also determined. The phosphors show a broad emission band from 320 nm to 475 nm. Due to the suitable emission wavelength range, the fast decay properties and relative low melting point, Na3 LuSi3 O9 :Ce 3+ may be a potential novel inorganic scintillator material.